Family Factors that Affect Family Empowerment in Caring Children with Leukemia - Arief, Yuni Sufyanti; nursalam, Nursalam; Ugrasena, I Dewa Gede; Devy, Shrimarti Rukmini; Saudah, Noer (Health Notions, 2018)
Introduction: Leukemia is one of the conditions of chronic disease in children. Families of children with chronic health conditions often feel helpless in meeting their childs health care needs. Powerlessness experienced by the family will affect the ability of families in providing care to their children. Many factors can affect the empowerment of families in providing care to their families. Method: This study aims to analyze family factors that affect family empowerment in treating children with leukemia leukemia. The research design used is explanation survey. The population in this study were families with children suffering from leukemia in Pediatric Ward RSUD Dr. Soetomo Surabaya. Result: The results showed that there was the influence of family factor to family empowerment in caring children with leukemia equal to t: 3.801. Discussion and Conclusions: Family factors need to be taken into account in family-centered empowerment, so families can improve their ability to care for leukemia children. Increased family-based health involves the strength and ability of families in coping mechanisms, the role of nurses, to encourage families to provide support in health care. More research is needed on family-centered empowerment models in the ability to care for children with leukemia. Factors that affect family empowerment in caring for child leukemia, can be considered nurse in giving nursing intervention especially child nurse in empowering parent at the time care of child leukemia. Keywords: Leukemia, Children, Family, Factor, Empowerment